2021
DOI: 10.1021/acssynbio.1c00481
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Functionally Enhanced α-l-Threofuranosyl Nucleic Acid Aptamers

Abstract: Synthetic genetic polymers (xeno-nucleic acids, XNAs) have the potential to transition aptamers from laboratory tools to therapeutic agents, but additional functionality is needed to compete with antibodies. Here, we describe the evolution of a biologically stable artificial genetic system composed of α-l-threofuranosyl nucleic acid (TNA) that facilitates the production of backbone- and base-modified aptamers termed “threomers” that function as high quality protein capture reagents. Threomers were discovered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 40 publications
1
47
0
Order By: Relevance
“…The work demonstrated that TNA could fold into tertiary structures with retained chemical functions, suggesting TNA as an RNA progenitor in the pre-RNA world. After that, various TNA aptamers with the capability of binding to small molecules and large proteins have been selected [ 178 , 179 , 180 , 181 , 182 , 183 ]. These TNA aptamers have remarkable thermal and biological stability.…”
Section: Chemically Modified Nucleic Acid Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…The work demonstrated that TNA could fold into tertiary structures with retained chemical functions, suggesting TNA as an RNA progenitor in the pre-RNA world. After that, various TNA aptamers with the capability of binding to small molecules and large proteins have been selected [ 178 , 179 , 180 , 181 , 182 , 183 ]. These TNA aptamers have remarkable thermal and biological stability.…”
Section: Chemically Modified Nucleic Acid Analoguesmentioning
confidence: 99%
“…( a ) Schematic illumination of TNA aptamer targeting PD-L1 for cancer immunotherapy. Reprinted with permission from [ 183 ]. Copyright 2020, Royal Society of Chemistry.…”
Section: Chemically Modified Nucleic Acid Analoguesmentioning
confidence: 99%
“…Different polymerases, including Therminator DNAP and a mutant of KOD DNAP, Kod-RI, have been used for the synthesis/transcription of TNA, and Bst DNAP has been used for the reverse transcription of TNA in these works. Recently, using TNA polymerase in combination with nucleobase-modified tNTPs, stable TNA aptamer with functionalized nucleobases have also been selected 202,203 . Mirror-image DNA has drawn broad interest in recent years, since it possesses good resistance to nucleases while retaining similar properties and functions of DNA 204 .…”
Section: Rsc Chemical Biology Accepted Manuscriptmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] To date, aptamers, XNAzymes, and nanostructures based on several different XNA systems have been reported, including 2 0 -deoxy-2 0 -uoroarabino nucleic acid (FANA), [12][13][14][15] hexitol nucleic acid (HNA), 16 locked nucleic acid (LNA), 17,18 and threose nucleic acid (TNA). [19][20][21][22] To enable the efficient uptake of XNA building blocks in the enzymatic polymerization reactions, engineered polymerases with altered substrate specicity were discovered through rational mutagenesis and directed evolution that can tolerate unnatural XNA nucleotide triphosphates (NTPs). For example, Holliger and coworkers evolved DNA polymerases that could recognize six classes of XNA NTPs including FANA, HNA, LNA, and TNA.…”
Section: Introductionmentioning
confidence: 99%